Comparative Studies on Physical Properties of Urine and Urine-Oxalic Acid Mixture of Healthy Individual and Patients Suffering from Urinary Calculi. - SHUKLA , P.C.; CHAUBE., D.K. (Asian Journal of Chemistry, 2010)
Physical properties such as density, viscosity, surface tension, pH, and specific electrical conductivity of urine of healthy individual and urine of patients suffering from gall bladder stones and kidney stones have been measured. It has been found that basic physical properties differ significantly in the case of healthy individual and those of people suffering from urinary calculi. Urines were incubated with goat bladder membranes to measure physical properties. It has been found that while density and specific electrical conductivity decrease continuously with increase in oxalic acid concentration in urine, other properties show oscillatory behaviour at certain concentrations of oxalic acid in urine.